DARK SECRETS OF THE ORACLE MONGER. (Skeptic, 2012)
The article discusses mystery from the ancient Roman Empire that is almost 2000 years ago. It is stated that during the 2nd Century C.E., the Roman Empire was in power, when people saw peace and prosperity; but in the absence of modern medicine, all Romans lived in fear of dangerous diseases. It is mentioned that after the death of his mentor, Alexander formed a partnership with a hustler, and the two went around the country practicing quackery and sorcery.